2018
DOI: 10.1159/000488841
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of LncDQ is Associated with Poor Prognosis and Promotes Tumor Progression via Epigenetic Regulation of the EMT Pathway in HCC

Abstract: Background/Aims: Long noncoding RNAs (lncRNAs) are key regulators of cancer initiation and progression. In this study, we investigated the clinical value and functional role of LncRNA DQ786243 (LncDQ) in the pathogenesis of hepatocellular carcinoma (HCC). Methods: To investigate the expression level of LncDQ in HCC, we performed quantitative real-time PCR using total RNA extracted from HCC tumor tissues and their matched non-neoplastic counterparts, as well as from the serum of HCC patients and healthy volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
0
18
1
Order By: Relevance
“…LncRNA MLK7-AS1 has been identified as one of the cancer-specific LncRNAs, its expression was significantly associated with the overall survival of patients with gastric cancer [ 5 ]. A recent study demonstrated that high MLK7-AS1 expression contributed to the proliferation and inhibited apoptosis of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNA MLK7-AS1 has been identified as one of the cancer-specific LncRNAs, its expression was significantly associated with the overall survival of patients with gastric cancer [ 5 ]. A recent study demonstrated that high MLK7-AS1 expression contributed to the proliferation and inhibited apoptosis of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The EMT process plays a crucial role during the progression of many types of cancers including human ovarian cancer [ 17 , 23 , 31 ]. Recent studies have demonstrated that LncRNAs are involved in regulation the EMT pathway [ 5 , 32 , 33 ]. In this study, our data also showed that knockdown of MLK7-AS1 upregulated epithelial maker expression levels but downregulated the expression levels of mesenchymal marker genes both in in vitro and vivo , while the suppression effects were partly reversed by miR-375-inhibition, indicating MLK7-AS1 might interact with miR-375 to promote cell proliferation via the EMT pathway in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of lncRNA Ftx promoted the proliferation, invasion and migration of HCC cells, while knockdown of lncRNA Ftx had the opposite effect [22,23]. In our previous studies, we also found that lncRNA DQ786243 was elevated in both HCC tissue samples and serum, which was associated with a low survival rate and poor clinicopathological characteristics [16]. In addition, multivariate analysis showed that lncRNA DQ786243 expression was an independent prognostic factor for HCC.…”
Section: Discussionmentioning
confidence: 69%
“…However, most of the lncRNA profiles in HCC remain largely unknown. In previous studies, we found that lncRNA DQ786243 plays an important role in the pathogenesis of HCC and promotes the development of HCC [16]. In the present study, we focused on lncRNA DQ679794 to identify the key lncRNA associated with HCC and to study its biological functions in HCC progression.…”
Section: Introductionmentioning
confidence: 92%
“…For instance, lncRNA mucin (MUC)5B-antisense non-coding RNA 1 enhances lung adenocarcinoma metastasis by regulating MUC5B expression (8). Overexpression of lncRNA DQ786243 predicts poor prognosis and contributes to the progression of hepatocellular carcinoma (HCC) (9). Cytoskeleton regulator RNA enhances glioma development via sponging microRNA (miR)-16 (10).…”
Section: Introductionmentioning
confidence: 99%